(3GdjJjes - (3TGfGb GdgfOjs
(3ChdgG (B:s
(3GdMeO ddg cKjQkG ceG gh Cgdg cGf TGfGb YXjekG ai GdgfO QajY GdbOQ YfO Cgd hgQg aCMO GdbSejf SQ ecJhe hGdCNQ LgGQ efXhQ s
(3BNQgG (B:s
(3bGd GdeCehf jfHZi Cf jSbW ef gPG GdcJGH fYJ GdLGQjI GdeSeheI dGf gPG aYd GdLGgdjI ef GdgfO Je cJGH TGfGb s
(3GdeNWhW YHGQI Yf GdfSNI GdSGdHI hGdehLHI dfaS GdcJGH GdcJGH NeS ebGdGJ hJe JQLeI ef GdgfOjI ddaGQSjI Ke ef GdaGQSjI Edi GdYQHjIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1425s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs